Structural study of the rare earth compounds: Sm(OH)3, NdOHCO3, CeO2, and Ho2O3, prepared by Chemical Bath Deposition, and its correlation with crystal growth mechanism (Superficies y Vacío, 2023)
We present the preliminary theoretical-experimental study of the structural properties for rare earths: hydroxide, hydroxycarbonate and Oxide; Sm(OH)3, NdOHCO3, CeO2, and Ho2O3 powders, respectively. In the experimental preparation, Chemical Bath Deposition (CBD) technique is applied at ~20 ±2 °C. In our experimental conditions, the parameters of crystal growth are: concentration of progenitor reagents, stirring, pH and temperature, remain constant. The chemical kinetics of crystal growth is systematically examined at key synthesis steps, considering the physicochemical and electrodynamic parameters: ionic radii, electron affinity, and hydration enthalpy of the rare earth (Sm3+, Nd3+, Ce3+, and Ho3+) cation. The main objective of this report is to investigate the theoretical-experimental correlation associated with the experimental conditions and the physicochemical parameters in the synthesis of hydroxide, hydrocarbonates and oxide. The crystallographic study of the powders is carried out using the X-ray Diffraction (XDR) technique. Analyzing the crystal phase, it is found that Sm(OH)3 and NdOHCO3 present hexagonal crystal phase, CeO2 and Ho2O3 are identified cubic crystal structure. The quantified grain size turns out to be: Sm(OH)3: ~1.40 - 2.03 nm, NdOHCO3: ~14.33 - 22.25 nm; CeO2: ~1.65 - 3.05 nm; and Ho2O3: ~3.72 - 6.08 nm. The Dislocation density (?) is: Sm(OH)3: ~2.47 - 5.10×1017 lines/m2; NdOHCO3: 2.01 - 4.68×1015 lines/m2; CeO2: 1.07 - 3.67×1017 lines/m2.